Feasibility and mechanism analysis of Reduning in the prevention of sepsis-induced pulmonary fibrosis - Wang, Ziyi; Liu, Yuxin; Chen, Feng; Liao, Haiyan; Wang, Xuesong; Guo, Zhe; Wang, Zhong (Frontiers in Pharmacology, 2022)
Introduction: The increasing mortality in patients with sepsis-induced pulmonary fibrosis owes to a lack of effective treatment options. This study aims to explore the possibility and possible targets of Reduning in the prevention of sepsis-related pulmonary fibrosis. Methods: The active components and targets of Reduning were searched and screened from the database and analysis platform of traditional Chinese medicine (TCM) system pharmacology. GeneCards, human genome database, DisGeNET database, and the OMIM database were checked to determine the targets associated with sepsis-induced pulmonary fibrosis. DAVID Bioinformatics Resources 6.8 was used for GO and KEGG enrichment analysis to predict its possible signaling pathways and explore its molecular mechanism. The protein–protein interaction (PPI) network was used to identify key active components and core targets. Molecular docking technology was applied to screen the complexes with stable binding of key active components and core targets. Molecular dynamics simulations were used to verify the binding stability and molecular dynamics characteristics of the complexes. The protective effect of RDN on sepsis-induced pulmonary fibrosis was verified by in vitro and in vivo experiments. Results: There were 319 shared targets between sepsis-induced pulmonary fibrosis and RDN. GO enrichment analysis showed that they mainly regulated and participated in the positive regulation of kinase activity, mitogen-activated protein kinase (MAPK) cascade, and protein phosphorylation. KEGG enrichment analysis showed that they were mainly enriched in the mitogen-activated protein kinase cascade signaling pathway, the calcium signaling pathway, the apoptosis pathway, and other signaling pathways. The results of molecular docking and molecular dynamics simulations showed that the active components, stigmasterol, beta-sitosterol, and quercetin, had good binding activities with ERBB2, and they exhibited good stability. Molecular validation experiments confirmed RDN could alleviate lung fibrosis induced by cecum ligation and puncture (CLP), in parallel with the inhibition of the ERBB2-p38 MAPK pathway in mouse alveolar macrophages (AMs). Discussion: Reduning may prevent sepsis-induced pulmonary fibrosis by regulating the ERBB2-p38 MAPK signaling pathway, which provides a possibility for the prevention of sepsis-induced pulmonary fibrosis with traditional Chinese medicine.